1825 N.H. Laws 74, § 3 - (:unkn) unknown (My University, 1825)
An Act to Regulate the Keeping and Selling, and Transporting of Gunpowder, § 3: Banned transport or carry of gunpowder through the compact part of any town or village in any cart, wagon, or other open carriage in quantities over 100 pounds at one time.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER